Early Marriage in the Islamic Legal System, the Continental and Anglo Saxon European Legal Systems - Muchamad Ikbal; Ah. Fathonih; Fauzan Ali Rasyid (An-Nisa: Journal of Islamic Family Law, 2025)
Child marriage is a violation of human rights that has a systemic impact on aspects of reproductive health, education, economy, and social participation. This article conducts a comparative-critical analysis of the construction of child marriage law in three dominant legal systems: Islamic Law (based on maslahah mursalah), Continental European Law (codification-based), and Anglo-Saxon Law (precedent-based), using the theoretical framework of legal pluralism Santos (1987) and the concept of best interest of the child (CRC 1989). The research method combines a normative-doctrinal approach with a critical discourse analysis of primary legal texts and court decisions in 15 representative countries. The findings reveal three paradigms: (1) Contemporary Islamic law has undergone a transformation from classical fiqh through the reinterpretation of maqashid shari'ah with an age limit of 18 years (Law No. 16/2019 in Indonesia and the Child's Rights Act 2003 in Nigeria); (2) The Continental European System implements legal paternalism through the harmonization of EU Directive 2019/51 with the minimum age standard of 18 years without dispensation; (3) The Anglo-Saxon system developed judicial activism through progressive precedents (the Re Marriage Act 2015 in the UK and Obergefell v. Hodges in the US). This study contributes to the theory of global legal convergence by recommending an integrated legal reform model that synthesizes the legal certainty of the European system, Anglo-Saxon flexibility, and Islamic maslahah values.